Philosophers of nothingness : an essay on the Kyoto school - Heisig, James W., 1944- (Nanzan library of Asian religion and culture., 2001)
The past twenty years have seen the publication of numerous translations and commentaries on the principal philosophers of the Kyoto School, but so far no general overview and evaluation of their thought has been available, either in Japanese or in Western languages. James Heisig, a longstanding participant in these efforts, has filled that gap with Philosophers of Nothingness. In this extensive study, the ideas of Nishida Kitaro, Tanabe Hajime, and Nishitani Keiji are presented both as a consistent school of thought in its own right and as a challenge to the Western philosophical tradition to open itself to the original contribution of Japan.